Faktor Penyebab Kesulitan Membaca dan Dampak terhadap Perkembangan Prestasi Siswa Kelas IV-VI SDN 104255 Pantai Labu - Salma Siregar; Fella Annisa Harahap; Danil Dalimunthe; Tri Bayu Purnama (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
The purpose of this research is to find out what causes reading difficulties and the impact on the development of learning outcomes or student achievement in grades IV-VI SDN 104255 Pantai Labu. Factors that cause students' reading difficulties are 1). Lack of attention from both parents and teachers, 2). No concentration, 3). Too much use of gadgets, 4). There is no supervision from parents at home, 5). The impact and influence obtained during the Covid atmosphere made all teaching and learning activities not optimal. By using qualitative research methods, researchers were able to obtain data using observation sheets and interviews with teachers. This research was conducted in class IV-VI SDN 104255 Pantai Labu, Deli Serdang Regency, North Sumatra Province using theme books as learning materials. The technique used by SDN 104255 is a conventional method (lecture method) which is used as one of the factors that makes it difficult for students to read. The sample from this study was around 100 students, of which there were around 20 students who had difficulty reading at SDN 104255. Therefore, it greatly affected student achievement or even failed to go to class. Therefore, actions and solutions are needed to overcome this so that it does not happen again. There must be attention from both parties, both parents and educators at school, of course. therefore, it can be concluded that the learning method used can affect the learning outcomes and persistence of a student to be good at reading.